Frontal Functional Connectivity of Electrocorticographic Delta and Theta Rhythms during Action Execution Versus Action Observation in Humans - Babiloni, Claudio; Del Percio, Claudio; Lopez, Susanna; Di Gennaro, Giancarlo; Quarato, Pier P.; Pavone, Luigi; Morace, Roberta; Soricelli, Andrea; Noce, Giuseppe; Esposito, Vincenzo; Gallese, Vittorio; Mirabella, Giovanni (Frontiers in Behavioral Neuroscience, 2017)
We have previously shown that in 7 drug-resistant epilepsy patients, both reaching-grasping of objects and the mere observation of those actions did desynchronize subdural electrocorticographic (ECoG) alpha (8-13 Hz) and beta (14-30) rhythms as a sign of cortical activation in primary somatosensory-motor, lateral premotor, and ventral prefrontal areas (Babiloni et al., 2016). Furthermore, that desynchronization was greater during action execution than during its observation. In the present exploratory study, we reanalyzed those ECoG data to evaluate the proof-of-concept that lagged linear connectivity between primary somatosensory-motor, lateral premotor, and ventral prefrontal areas would be enhanced during the action execution compared to the mere observation due to a greater flow of visual and somatomotor information. Results showed that the delta-theta (< 8 Hz) lagged linear connectivity between lateral premotor and ventral prefrontal areas was higher during action execution than during action observation. Furthermore, the phase of these delta-theta rhythms entrained the local event-related connectivity of alpha and beta rhythms. It was speculated the existence of a multi-oscillatory functional network between high-order frontal motor areas which should be more involved during the actual reaching-grasping of objects compared to its mere observation. Future studies in a larger population should cross-validate these preliminary results.